Development of Student Worksheets for Inquiry Model in Differentiated Learning to Improve Students' Critical Thinking - Aeti, Siti; Sumarno, Sumarno; Dwijayanti, Ida (Papanda Publisher, 2025)
Conditions of grade V students of SDN Kubangjati 02 have an impact on the low scores of computer-based national assessments and education report cards. To overcome this problem, a learning model was developed to stimulate students' critical thinking process by using Student Worksheets (LKPD) in differentiated learning through the inquiry learning model. This study aims to analyze the effectiveness of the LKS device in differentiated learning through the inquiry learning model to improve students' critical thinking processes and abilities. The type of research used is development research. The data collection techniques used are tests, interviews, questionnaires, and documentation. The data analysis techniques used are normality tests, homogeneity tests, paired sample t-tests, and N-Gain tests. The results of the practicality test of the developed LKS student response questionnaire were stated to be practical by students with an average score of 91.4 and were categorized as very good. The output results of